Journalism and Propaganda in Peru. A complex relationship during election campaign - Hinojosa Navarro, Ghiovani (2014)
10 April 2016 will be the presidential election in Peru. The media will cover the activities of the leading candidates and rummage in their resumes. In this process, the press will be tempted to use propaganda techniques, a category traditionally associated with political actors. For example, they may appeal to stereotypes, express their opinion through seemingly independent sources and select facts to build an ideological discourse. For its part the press agents of candidates and political marketing experts are hunting for journalists.